MENINGKATKAN HASIL BELAJAR MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD, SNOWBALL THROWING, PICTURE AND PICTURE SDN PEMBANTANAN 1 KABUPATEN BANJAR - Stevie Nur Mayanda Yani; Amberansyah (STKIP Subang, 2026)
The study aims to investigate learning objectives, practice questions,and critical thinkingskills related to the animal life cycle curriculum for fourth-grade students at SDNPembantaian 1 Sungai Tabuk. Using both qualitative and quantitative researchapproaches,the study conducted Classroom Action Research (CAR) in four meetings with18 fourth-grade students as subjects, even during the 2023-2024 semester. The researchfindings showed that instructor activity increased from a score of 17 to 30 for meetings1-4, student participation increased from 28% to 100% in meetings 1-4, the criticalthinking component increased from 28% to 100% in meetings 1-4, and learningoutcomes increased from 50% to 100% in meetings 1-4.